Resonant Alfvén Waves in the Lower Auroral Ionosphere: Evidence for the Nonlinear Evolution of the Ionospheric Feedback Instability. Issue 2 (2nd February 2022) - Akbari, Hassanali; Pfaff, Robert; Clemmons, James; Freudenreich, Henry; Rowland, Douglas; Streltsov, Anatoly
Abstract: During the "Auroral Jets" experiment from Poker Flat, Alaska on 2 March 2017, two NASA sounding rockets were simultaneously launched into the active auroral ionosphere. The rockets were equipped with instrumentation to measure DC and AC electric fields, magnetic fields, energetic electrons, plasma density, and neutral winds and achieved apogees of 190 and 330 km. A prominent feature of the electric and magnetic field observations is the presence of localized large‐amplitude (±40 mV/m and ±100 nT) small‐scale ( λ ⊥ ∼ 1 km) Alfvén wave structures at altitudes as low as 150 km in the vicinity of up‐ and down‐ward current regions. We interpret the oscillations as representing standing waves associated with the ionospheric Alfvén resonator formed between the ionosphere and the lower magnetosphere. The electric field components of the Alfvén waves show signatures of wave steepening in correlation with electron precipitation and large variations of the background plasma density. The signatures are discussed in the context of nonlinear evolution of the ionospheric feedback instability. Key Points: Localized large‐amplitude Alfvén wave structures are observed simultaneously at two altitudes in dual‐sounding rocket experiment Observations are interpreted as standing Alfvén waves "trapped" in the ionosphere and subjected to the ionospheric feedback instability Observations reveal signatures of nonlinear wave steepening in correlation with large variations of the background plasma density